A case of liver abscess and fusobacterium septicemia. (2017) - Rahmati, Elham; She, Rosemary C.; Kazmierski, Brittany; Geiseler, P. Jan; Wong, Darren
Abstract: Fusobacterium species are well described as the causative pathogen in Lemierre's syndrome, a suppurative thrombophlebitis of the jugular vein. However, they are less recognized for a unique variant of Lemierre's syndrome presenting with invasive intraabdominal infection and associated portal vein thrombosis. We describe a case of Fusobacterium nucleatum with hepatic abscess and septic pylephlebitis.